The Role of Hemoglobin in Maintaining Health: A Literature Review - Agesti, Nireza; Damrah, Damrah; Rasyid, Willadi; Welis, Wilda; Rahman, Dally; Zarya, Fiky (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
The role of hemoglobin in maintaining health is still not fully understood Thoroughly. Therefore, this literature review aims to uncover comprehensively the role of hemoglobin in maintaining health. Objective: The purpose of this literature review is to investigate the role of hemoglobin in maintaining health by collecting and analyzing current findings in the scientific literature. The methodology used is a systematic search through academic databases such as PubMed, Google Scholar, and Scopus using relevant keywords such as